151 Symptom management in end stage liver disease – results of a regional palliative care network survey. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Ting, G; Foster, D; Fradsham, S; Henry, J; Hill, J; Howarth, S; Owens, L; Rugen, K; Khodabukus, A
Abstract : Background: Symptom management in patients with end-stage liver disease can be challenging due to hepatic dysfunction. The aim of this study was to scrutinise the literature and current practices among healthcare professionals leading to the development of regional standards and guidelines. Method: A systematic review of the literature was undertaken to look for evidence of best practice in the management of common symptoms seen at the end of life in this patient cohort. In addition, this review assessed patient experience of living and dying with end-stage liver disease. To evaluate local clinical practices and professional needs, healthcare professionals in the Mersey and Cheshire regional palliative care network were surveyed. This survey was supplemented by a retrospective case note review of patients with end-stage liver disease known to palliative care teams in the hospital, hospice and community. Results: The literature review found little robust evidence for managing commonly encountered symptoms in patients with end-stage liver disease at the end of life. Fifty-one healthcare professionals (31 doctors, 19 nurses, 1 pharmacist) were surveyed. The majority of responders highlighted a need for up-to-date training in pharmacology specific to end-stage liver disease. Midazolam was most frequently prescribed to manage agitation. Forty-eight case notes were reviewed. Twenty-six (54%) patients had evidence of hepatic encephalopathy at the time of their admission. In 38% of the cases, Lactulose was used and in 23% of the cases, benzodiazepines were used. In 88% cases, terminal agitation was managed with Midazolam and in 15% cases, Levomepromazine was used. Conclusion: There is clearly a need for greater awareness of the pharmacology in symptom control in end-stage liver disease. As a result of this study, peer-reviewed clinical standards and guidelines are being formulated for the management of specific symptoms related to end-stage liver disease to provide standardised care across the network.